Corn Yield Response to Deep Subsurface Drip Irrigation in the Southeast. Issue 1 (22nd January 2013) - Sorensen, Ronald B.; Butts, Christopher L.; Lamb, Marshall C.
Abstract : Long term grain corn ( Zea mays L.) yield with various crop rotations irrigated with subsurface drip irrigation (SSDI) is not known for southeast United States. A subsurface drip irrigation system was installed on Tifton loamy sand with three crop rotations, two drip tube lateral spacings, and three irrigation levels. Crop rotations were alternate year, back‐to‐back, and three years between corn crops. Drip tube laterals were installed underneath each crop row (narrow) and alternate row middles (wide). Crops were irrigated daily at 100, 75, and 50% of estimated crop water use. Irrigation level affected corn yield 6 out of 8 years with 50% irrigation level having lower yield compared with 75 or 100% irrigation level. The 50% irrigation level averaged 7327 kg/ha while the 75 and 100% irrigation levels averaged 9334 and 9691 kg/ha, respectively. The narrow lateral spacing increased corn grain yield 50% of the time but the higher yield may not offset the cost of the increased tubing compared with the wider lateral spacing. There is no clear evidence indicating one specific crop rotation better than another. Applying irrigation at 75% of recommended water use did not reduce crop yield, implying a possible 25% water savings compared with full irrigation.